THE EFFECT OF CHITOSAN COATING ON COLOR AND BRIX OF RED GRAPES (Vitis vinivera) IN STORAGE - Andra Tersiana Wati; Elok Pawening Maharani (The University of Lampung, 2020)
Fruits are a type of perishable agricultural product. One of the post-harvest handling efforts to maintain the freshness of the fruit is chitosan coating. Research has been carried out on various level concentration of chitosan as a coating for grapes (Vitis vinifera) and storage time. This study aims to determine the effect of chitosan concentration on water content, color and brix of red grapes after storage. Chitosan coating was carried out by immersion methods at various levels of chitosan concentration, namely 0%, 0.5%, 1%, 1.5% and 2% (w/v) with immersion times of 30 seconds and 60 seconds. Based on the statistical test, it is shown that the chitosan concentration of 1.5% (w/v) with immersion time of 60 seconds and storage time on the 5th day is the most optimum for the brightness level of the grapes because the chitosan layer can close the pores of red grapes so that the respiration process aerobic and CO2 which affect color can be inhibited by chitosan solution. Keywords: Chitosan, edible coating, grape, post harvest, shelf life